2016
DOI: 10.1155/2016/3281975
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination among Pregnant Women: Patient Beliefs and Medical Provider Practices

Abstract: ACOG's research department recruited four medical centers to participate in a study on the attitudes and practices of medical providers and pregnant patients regarding influenza vaccination. Medical providers and patients were given voluntary surveys and medical record data was collected over two flu seasons, from 2013 to 2015. Discrepancies between self-reports of medical providers and patients and medical records were observed. Nearly 80% of patients self-reported accepting the influenza vaccine, but medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 5 publications
7
36
1
1
Order By: Relevance
“…Our results are in agreement with previous studies that show that a compelling recommendation from a provider is one of the most important factors in a pregnant woman's decision to get vaccinated [20,24,[26][27][28][29]. Indeed, our study identi ed that the lack of recommendation was a barrier for vaccination among pregnant women.…”
Section: Discusionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with previous studies that show that a compelling recommendation from a provider is one of the most important factors in a pregnant woman's decision to get vaccinated [20,24,[26][27][28][29]. Indeed, our study identi ed that the lack of recommendation was a barrier for vaccination among pregnant women.…”
Section: Discusionsupporting
confidence: 93%
“…Many studies have tried to determine the factors in uencing coverage of vaccination against in uenza during pregnancy. Different authors have highlighted that vaccination recommendation by health professionals is the main reason why pregnant women chose to be vaccinated against in uenza [16][17][18][19][20]. Other studies have identi ed additional in uences such as: socio-economic characteristics, fear of side effects, doubts about the safety and effectiveness of the vaccine, fear of needles/pain or under-estimation of personal risk [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in agreement with previous studies that show that a compelling recommendation from a provider is one of the most important factors in a pregnant woman's decision to get vaccinated (19,29,(32)(33)(34)(35)(36)(37)(38). Indeed, our study identi ed that the lack of recommendation was a barrier for vaccination among pregnant women.…”
Section: Discusionsupporting
confidence: 93%
“…This might be partly attributable to differences in perception among patients and providers of a recommendation for or offer of vaccination. In a recent survey of obstetric care providers conducted by the American College of Obstetricians and Gynecologists (ACOG), all surveyed providers reported that they recommend influenza vaccine to their pregnant patients; however, only 85% of patients surveyed at the same practices reported receiving a recommendation for vaccination, suggesting that although providers believe they are giving a recommendation for vaccination, the recommendation might not be communicated effectively ( 5 ). …”
Section: Discussionmentioning
confidence: 99%